Adaptive capacity to climate change in the wine industry: A Bayesian Network approach - Eva Merloni; Luca Camanzi; Luca Mulazzani; Giulio Malorgio (Wine Economics and Policy, 2018)
This study assesses the main factors influencing the behavior of wine producers and the strategies implemented by them with regard to changing climatic conditions. To do so, we adopted a Bayesian Network combining climatic, technical, and economic factors, as well as farmer perception and environmental actions. Based on the scientific literature reviewed, a set of research hypotheses was formulated and compared with empirical evidence collected in the Italian region of Emilia-Romagna. Climatic data, both at the regional and vineyard levels were collected and primary information on wine growing and wine making firms was gathered by means of a producer survey, including 56 wine farms. The results showed that the probability to be negatively affected by the effects of climate change is influenced by structural and technical farm characteristics and by farmer readiness to embrace change. Local climatic conditions, particularly temperature and water surplus, are the factors that most affect both wine production and adaptation behavior in the study area. We conclude that the adoption of focused management and appropriate adaptation strategies, as well as appropriate policies with regard to regulation, incentives and support, are crucial issues for farmers to face the ongoing climatic challenge.
Keywords: 330; Adaptive capacity; Bayesian Network; Climate change; Wine sector